упростите выражение:

ctg(п-а)+tg(-а)/ctg(a+3п)-tg(a+2п=

sin(п+а) sin(а-п) cos(2п-а) tg(3п-а)/cos( п-а) cos(а-5п) cos(2п+а) tg(-а-п)=
(п-означает пи,а-означает альфп)

2

Ответы и объяснения

2013-02-10T08:40:02+00:00

ctg(п-а)+tg(-а)/ctg(a+3п)-tg(a+2п=-ctga-tga/tga-tga=-ctga-1-tga

sin(п+а) sin(а-п) cos(2п-а) tg(3п-а)/cos( п-а) cos(а-5п) cos(2п+а) tg(-а-п)=-sina*-sina*cosa*-tga/-cosa*-cosa*-tga=-sin^2a*cosa/-cos^2a=tg^2a*cosa

Лучший Ответ!
  • Участник Знаний
2013-02-10T08:42:31+00:00

ctg(п-а)+tg(-а)                      -ctga-tga         

----------------------------- = --------------------

ctg(a+3п)-tg(a+2п)               ctga-tga